TGFβ Inhibition Stimulates Collagen Maturation to Enhance Bone Repair and Fracture Resistance in a Murine Myeloma Model. (31st October 2019) - Green, Alanna C; Lath, Darren; Hudson, Katie; Walkley, Brant; Down, Jennifer M; Owen, Robert; Evans, Holly R; Paton‐Hough, Julia; Reilly, Gwendolen C; Lawson, Michelle A; Chantry, Andrew D
ABSTRACT: Multiple myeloma is a plasma cell malignancy that causes debilitating bone disease and fractures, in which TGFβ plays a central role. Current treatments do not repair existing damage and fractures remain a common occurrence. We developed a novel low tumor phase murine model mimicking the plateau phase in patients as we hypothesized this would be an ideal time to treat with a bone anabolic. Using in vivo μCT we show substantial and rapid bone lesion repair (and prevention) driven by SD‐208 (TGFβ receptor I kinase inhibitor) and chemotherapy (bortezomib and lenalidomide) in mice with human U266‐GFP‐luc myeloma. We discovered that lesion repair occurred via an intramembranous fracture repair‐like mechanism and that SD‐208 enhanced collagen matrix maturation to significantly improve fracture resistance. Lesion healing was associated with VEGFA expression in woven bone, reduced osteocyte‐derived PTHrP, increased osteoblasts, decreased osteoclasts, and lower serum tartrate‐resistant acid phosphatase 5b (TRACP‐5b). SD‐208 also completely prevented bone lesion development in mice with aggressive JJN3 tumors, and was more effective than an anti‐TGFβ neutralizing antibody (1D11). We also discovered that SD‐208 promoted osteoblastic differentiation (and overcame the TGFβ‐induced block in osteoblastogenesis) in myeloma patient bone marrow stromal cells in vitro, comparable to normal donors. The improved bone quality and fracture‐resistance with SD‐208 provides incentive for clinical translation to improve myeloma patient quality of life by reducing fracture risk and fatality. © 2019 American Society for Bone and Mineral Research.